The antibacterial activity of Iranian plants extracts against metallo beta-lactamase producing Pseudomonas aeruginosa strains - Heidary, Mohsen; Hashemi, Ali; Goudarzi, Hossein; Khoshnood, Saeed; Roshani, Mahdaneh; Azimi, Hadi; Goudarzi, Mehdi (Archives of Advances in Biosciences, 2016)
Metallo β-lactamases (MBLs) producing Pseudomonas aeruginosa (P. aeruginosa) isolates are becoming an escalating global threat. Among the antibiotics used to treat infections associated with P. aeruginosa, resistance to carbapenem is a serious therapeutic challenge. The aim of the present study was to detect MBL-producing P. aeruginosa and to evaluate the extracts of Urtica. dioica, Carum. copticum, and Zataria multiﬂora on these clinical pathogens. The study was performed on hospitalized burn patients during 2014. Antibiotic susceptibility testing was tested by broth micro dilution and disc diffusion methods. The MBLs were detected using combination disk diffusion test (CDDT) phenotypically. Then, PCR and sequencing methods were carried out to detect the MBL encoding genes. Among 83 imipenem resistant P. aeruginosa strains, 48 (57.9%) isolates were MBL-producing P. aeruginosa. PCR and sequencing methods confirmed that these strains were blaIMP-1positive genes, whereas none were positive for blaVIM genes. Hospitalized burn patients with MBL-producing P.aeruginosa infection had 4/48 (8.3%) mortality rate. It was demonstrated that C. copticum, U. dioica, and Z. multiﬂora extracts had significant antibacterial effects on regular and IMP-producing P. aeruginosa strains. The prevalence of MBL-producing P .aeruginosa isolates in burn patients is very high. In this study, all MBL-producing strains encode the blaIMP-1gene. Therefore, detection of MBL-producing strains has major importance in identifying drug resistance patterns in P. aeruginosa and in controlling of infections. In the current study, the extracts from C. copticum, U. dioica, and Z. multiﬂora had high antibacterial effects against β-lactamase producing P. aeruginosa isolates.